Bacterial communities during composting cultivation of oyster mushroom Pleurotus floridanus using broken eggs as the nitrogen source and study of agronomic and nutritional properties - Wei, Jun; Wang, Yue-Xin; Guan, Ti-Kun; Wang, Qiu-Ying; Zhang, Jiao; Zhang, Jia-Yan; Wang, Jian-Li; Chen, Qing-Jun; Zhang, Guo-Qing (Frontiers in Microbiology, 2024)
Broken eggs are a byproduct of the poultry industry and a potential nitrogen source for mushroom cultivation. However, its feasibility needs to be evaluated experimentally.In this study, a series of different addition amounts (0, 1.8, 3.6, 5.3 and 8.5%, w/w) of broken egg mixture (BEM) were applied in the composting cultivation process of oyster mushroom. The physicochemical properties and bacterial communities of composting substrate, and agronomic and nutritional properties of fruiting bodies were determined.The results showed that the BEM addition significantly (P < 0.05) increased the total nitrogen content in the composted substrate, and the contents of crude protein, total amino acids and essential amino acids of mushrooms. The P3 treatment (initial C/N of 26:1) showed the highest biological efficiency (BE) of 100.19% and a low contamination rate (CR) of 7.00%, while the higher dosage of BEM (P4 and P5) led to a sharp decrease in BE and a sharp increase in CR. High throughput sequencing revealed that the addition of BEM significantly (P < 0.05) changed the bacterial communities in the substrate at the beginning of composting. Streptococcus and Lactococcus were predominant bacterial genera in BEM treatments at the beginning stage of composting, while Acinetobacter became predominant at the ending stage. The co-occurrence network analysis showed that the P3 treatment demonstrated a much more complex bacterial community. The structural equation model analysis indicated that the addition of BEM affected the bacterial communities and nitrogen metabolism during composting, which further affected agronomic and nutritional properties of oyster mushrooms. An appropriate amount of BEM combined with composting processes can significantly improve the yield and quality of oyster mushroom, providing a new way for efficient utilization of BEM.